2015
DOI: 10.1111/jels.12081
|View full text |Cite
|
Sign up to set email alerts
|

“Too Many Notes”? An Empirical Study of Advocacy in Federal Appeals

Abstract: The warp and woof of U.S. law are threaded by the appellate courts, generating precedents on constitutional provisions, statutory texts, and common-law doctrines. Although the product of the appellate courts is regularly the subject of empirical study, less attention has been given to the sources and methods of appellate advocacy. Given the paramount place of written briefs in the appellate process, we should examine seriously the frequent complaint by appellate judges that briefs are too long and that prolixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…In prior research on civil appeals, Sisk and Heise (2015:580) emphasized brief length and attorney experience. That study of Ninth Circuit appeals found that longer appellant‐side briefs were associated with judge votes to reverse.…”
Section: Practice Theory and Prior Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior research on civil appeals, Sisk and Heise (2015:580) emphasized brief length and attorney experience. That study of Ninth Circuit appeals found that longer appellant‐side briefs were associated with judge votes to reverse.…”
Section: Practice Theory and Prior Researchmentioning
confidence: 99%
“…Those studies are consistent with the possibility that information loads, advocate skills, and sequences all matter to outcomes. Appellate judges might pay most attention to the principal brief on the appellant's side in searching for a plausible case for reversal (Sisk & Heise 2015:596), then turn especially to oral argument, when available, and the appellee's attorney for a convincing response. Compare the idea that the appellant's brief sets the agenda of issues (Haire & Moyer 2008), and that “the sequential process of filing briefs places more of the burden of transforming a case from the trial posture on the appellant's attorneys” (Moyer et al 2013:73).…”
Section: Practice Theory and Prior Researchmentioning
confidence: 99%
See 3 more Smart Citations